Carbon stored in an agroforestry plot under the Sowing Life Program in Huehuetán - Marroquín-Morales, Pablo; Barrios-Calderón, Romeo de Jesús; González-Pérez, José Daniel; Osorio-Espinoza, Humberto; Gabriel-Hernández, Magdiel; Reyes-Reyes, Jorge (Revista Mexicana de Ciencias Agrícolas, 2026)
Climate change today constitutes a substantial threat to living beings. Human activities such as the use of fossil fuels, burning, the use of chemicals, and mainly deforestation contribute to the emission of greenhouse gases. In response to this, in Mexico, governmental, national, and environmental programs have been implemented that establish schemes in conjunction with producers in which various social, economic, and environmental benefits are obtained, and whose main objective is to reduce the environmental impact, as is the case with the Sowing Life Program. Agroforestry systems are considered a relevant system to face climate change through the biomass and carbon content of the different plant strata in these agroecosystems. The research estimated the indirect carbon storage in the agroforestry system, with a total of 15 sites measuring 4 x 25 m; the plot is a participant in the Sowing Life Program in the locality of San José El Amate (Huehuetán, Chiapas); once these data have been collected, biomass, carbon, and carbon dioxide were obtained through allometric equations. The agroforestry plot studied has a reserve of 22.6 t ha-1 of aboveground biomass, 8.75 t ha-1 of carbon and 32.14 t ha-1 of carbon dioxide.
Keywords: aboveground biomass; allometric models; climate change; mitigation